Contrast volume to estimated glomerular filtration rate ratio for prediction of contrast‐induced acute kidney injury after cardiac catheterization in adults with congenital heart disease. Issue 7 (9th September 2018) - Gellis, Laura; Gauvreau, Kimberlee; Ferguson, Michael; Bergersen, Lisa; Shafer, Keri; Porras, Diego
Abstract: Background: Adults with congenital heart disease (ACHD) are vulnerable to contrast‐induced acute kidney injury (CI‐AKI) after cardiac catheterization. The aim of this study was to identify risk factors for clinically significant CI‐AKI and evaluate the predictive value of contrast volume to estimated glomerular filtration rate ratio (V/eGFR) for the risk of CI‐AKI following catheterization in the ACHD population. Methods: ACHD patients who underwent catheterization at Boston Children's hospital between 1/2011 and 1/2017 were retrospectively analyzed. CI‐AKI was defined as an increase in serum creatinine ≥0.3 mg/dL within 48 hr or ≥1.5 times baseline within 7 days of procedure. Controls without CI‐AKI were matched for calendar year of catheterization with cases using a 3:1 ratio. Results: Of 453 catheterizations meeting inclusion criteria, 27 catheterizations (5.9%) were complicated by CI‐AKI, with dialysis being used to manage renal dysfunction in five of these events. Older age, male gender, admission prior to catheterization, and V/eGFR ratio were found to be related to risk of CI‐AKI. Patients with a V/eGFR ≥ 2.6 had a significantly higher risk of CI‐AKI (OR = 6.4; 95% CI = 2.0–20.4; P = 0.002). Survival at 3 years post‐catheterization, was significantly shorter for CI‐AKI cases compared to controls (49% versus 97%; P < 0.001) even in those with return to baseline renal function prior to discharge (60% versus 97%, P < 0.001). Conclusion: In ACHD patients undergoing cardiac catheterization, a higher V/eGFR ratio is a strong predictor of clinically significant CI‐AKI. Development of CI‐AKI is a poor prognostic indicator and is associated with decreased survival in this population.